Toward Gender Equality in Education—Teachers’ Beliefs about Gender and Math - Jana Lindner; Elena Makarova; Deborah Bernhard; Dorothee Brovelli (Education Sciences, 2022)
Math has a strong gender-related image, even among teachers. As teachers hold beliefs about their work, their role, their subject, and their students, they shape girls’ and boys’ mathematical beliefs and attitudes. Research during the past 20 years has shown that teachers’ gender beliefs about mathematics significantly favor boys, thereby reinforcing girls’ low math ability self-concept. Still, there is a lack of studies that examine teachers’ gender-related beliefs based on their underlying assumptions. Our study provides the first empirical evidence of the relationship between general gender stereotypes and math stereotypes. To this end, we used partial correlation and MANCOVA to analyze data from an online survey in 2019/2020 conducted in Switzerland (195 women, 80 men) as part of a cross-cultural comparison study. We therefore created a differentiated profile of prospective teachers by examining their beliefs about their self-image, their image of men and women in society, their essentialist and gender role ideology beliefs, and their math stereotypes. Then, we linked prospective teachers’ beliefs about gender (based on 48 characteristics) to their beliefs about mathematics and about girls’ and boys’ competencies in math. The extensive analysis provides knowledge about prospective teachers and is particularly important for teacher education.